(untitled) (Research, Society and Development, 2023)
Cervical cancer (CC) is a global public health problem, requiring further intensification of screening programs. Thus, the objective was to analyze the knowledge of medical students about the prevention of cervical cancer. This is a quantitative, cross-sectional and descriptive study, which was carried out between June and August 2022, with medical students from a private university in Teresina-PI, who were studying between the third and twelfth period, totaling, totaling 318 academics. Data were collected through a questionnaire sent by Google Forms. The sample consisted predominantly of female students, with a mean age of 24.4 years, attending the 7th period of the course. In addition, about 292 (92.1%) participants reported already having sexual activity, 208 (65.4%) were vaccinated against HPV. It was possible to identify that 182 (57.6%) make regular use of condoms and 156 (50.6%) reported having already undergone a screening test for cervical cancer. The knowledge of academics in relation to cervical cancer was satisfactory, when comparing the most prevalent answers with the literature, and it was not possible to make a comparison of this item between periods, due to the different number of participants. Therefore, it is believed that understanding the level of knowledge of academics about cervical prevention in a multidisciplinary perspective is essential for future professionals to be able to make appropriate and evidence-based health care choices.